More than a number: clarifying the dates of publication of some papers of A. Doering on land and freshwater shells from Argentina and a note on his taxon Clessinia (Odontostomidae) - Breure, Abraham S. H.; Miquel, Sergio E. (Zootaxa, 2012)
The dates of publication of ten papers of A. Doering published from 1874–1879 in two Argentinan journals are reviewed.Seven of these papers appear to have been published later than their printed dates suggest. The status of one taxon described in these papers, Clessinia Doering, 1875, is clarified.